Etika Politik dalam Sejarah Umat Islam - Susmihara Susmihara (Universitas Islam Negeri Alauddin Makassar, 2015)
The purpose of this essay is trying to observe the concept of political ethics in Islam within history of Islam community. The writer intentions to describe it until there are no less understanding about it. Right now, the political situation aborts the ethical concept of Islam. Actually it appears because our overview by the political treatise which defines politics as a way to seize the power with any circumstances. Probably, the other reason on why it happens, because we don’t reflect the way of our former throughout Islamic history. On this essay, it will be found that the balance of a state depends on the implementation of ethical value by the government in every event of Islamic community throughout history. The result of this implementation will make a civil society, like in the City of Madinah on the era of Muhammad saw. However, it doesn’t mean that the ethical value of Islam is only able for the society on the era of Muhammad because Islam ethical value prevails on the universal life. Furthermore, the Islamic ethical value is also implemented on after the era of Muhammad. It can be seen on the age of Caliphs or the era of each leaders of Islamic state. Beside it we will find, every conceptual of Islam political ethics in each treatises of classic Islamic scholars, like al-Ghazali, al-Mawardi, Ibn Taimiyah or the Islamic philosophers. Finally, the political ethics of Islam aims to ensure the right’s of people and to carry out the commandment of Allah swt.